Współczynnik kosztów materialnych jako kryterium optymalnej struktury eksportu - Kulik, Czesław (Wydział Prawa i Administracji UAM, 1966)
The production and export of the goods with a high extent of processing are determined by the limited reserves of raw materials and a relatively speedy growth of the population in Poland. The increase in the export of highly processed products results in the growing revenue of foreign currency per unit of raw materials. Hence, all the decisions concerning export should (not pointing out other criteria) be based on the analysis of material costs in individual branches of the national economy. If the possibility of making choice exists, it should bë guided by the principle of the amount of material cost per unit of value (the lower cost the better). In connection with this, it is necessary to classify all the goods, as well as branches of the national economy according to the share of material costs in the value of goods. The author, next discusses in detail the above problems and attemps to classify individual branches of the national economy in accordance with the share of material costs indices. The article is provided with various detailed calculations and concrete examples.